SWOT Analysis of Financial Technilogy Implementation on The Quality of Banking Services in Indonesia - Yayah Ikhda Nevia (STIKes Ibnu Sina Ajibarang, 2024)
The implementation of financial technology (FinTech) has significantly transformed the banking sector in Indonesia, impacting the quality and accessibility of services offered. This study examines the strengths, weaknesses, opportunities, and threats (SWOT) associated with the adoption of FinTech in the banking industry. Using a qualitative approach, data was collected from industry reports, case studies, and expert interviews to provide a comprehensive analysis. The results highlight several strengths, including improved efficiency, enhanced customer experience, and expanded financial inclusion. However, weaknesses such as high operational costs and cybersecurity risks remain prevalent. Opportunities for growth lie in the increasing digital literacy and government support, while threats include intense competition and regulatory challenges. This study concludes that while FinTech presents significant potential to elevate banking service quality in Indonesia, its success depends on addressing key challenges through strategic innovation and robust policy frameworks.